Colonoscopy and reduction of colorectal cancer risk by molecular tumor subtypes: a population-based case-control study - Hoffmeister, Michael; Bläker, Hendrik; Jansen, Lina; Alwers, Elizabeth; Amitay, Efrat L.; Carr, Prudence R.; Kloor, Matthias; Herpel, Esther; Roth, Wilfried; Chang-Claude, Jenny; Brenner, Hermann (The American journal of gastroenterology, 2020)
INTRODUCTION: - In previous studies, the protective effect of colonoscopy was generally stronger for distal colorectal cancer than for proximal colorectal cancer (CRC). This study aimed to investigate whether reduction of CRC risk through colonoscopy varies according to major tumor markers and pathways of CRC. - METHODS: - This is a population-based case-control study from Germany, including 2,132 patients with a first diagnosis of CRC and information on major molecular tumor markers and 2,486 control participants without CRC. Detailed participant characteristics were collected by standardized questionnaires. Information on previous colonoscopy was derived from medical records. Polytomous logistic regression was used to calculate adjusted odds ratios (ORs) and 95% confidence intervals (CIs) for the association between previous colonoscopy and subtypes of CRC. - RESULTS: - Overall, we observed strong risk reduction of CRC after colonoscopy that was weaker for microsatellite instable (MSI) than for non-MSI CRC (OR 0.70, 95% CI 0.50-0.97 vs OR 0.28, 95% CI 0.24-0.33), for CpG island methylator phenotype high CRC than for CpG island methylator phenotype low/negative CRC (OR 0.45, 95% CI 0.34-0.59 vs OR 0.29, 95% CI 0.25-0.34), for BRAF-mutated than for BRAF nonmutated CRC (OR 0.62, 95% CI 0.42-0.91 vs OR 0.30, 95% CI 0.25-0.35), for KRAS nonmutated than for KRAS-mutated CRC (OR 0.34, 95% CI 0.29-0.40 vs OR 0.26, 95% CI 0.20-0.32), and for CRC classified into the sessile serrated pathway than for CRC of the traditional pathway (OR 0.57, 95% CI 0.36-0.91 vs OR 0.30, 95% CI 0.25-0.37). After colonoscopy with the detection of adenomas or hyperplastic polyps, no risk reduction was found for sessile serrated pathway CRC, MSI, and BRAF-mutated subtypes. - DISCUSSION: - Our study extends the molecular understanding of existing differences in risk reduction of proximal and distal CRCs reported by previous studies and may imply important information for improving strategies for timely detection of relevant precursors.
Gesehen am 03.03.2021